Lessons to be learnt from the COVID-19 public health response in Mauritius (2020)
Objectives: This study had the following objectives: (1) To look into the public health response of the country facing the COVID-19 outbreak, and (2) To examine the effectiveness of the measures being undertaken to contain the outbreak. Methods: The research method used was the analysis of all documents/discourses pertaining to the public health response of Mauritius towards COVID-19. We compiled data over the period of 17 January 2020 to 15 May 2020 as and when they were communicated. Results: This study revealed three main themes: (1) Prevention strategy, (2) Outbreak management strategy and (3) Communication strategy. In light of the qualitative findings and the numerical data provided by the Mauritian authorities, we appraise the public health response of Mauritius. Conclusions: After demonstrating the effectiveness of the public health strategies undertaken by the Mauritian government, we draw the lessons learnt from the experience of Mauritius. These lessons have implications for practice by middle-income countries and/or small island developing states facing a communicable disease outbreak.